Strategies for Marketing Djuanda Forest Park in the Effort to Increase the Number of Visitors - Ratu Ratna Mulyati Karsiwi; Nurlena Nurlena (Institut Pariwisata dan Bisnis Internasional, 2021)
Djuanda Forest Park as a conservation forest has great potential as a tourist destination because there are a lot of attractions in one area. Nevertheless, the number of domestic and foreign visitors in several months is still low. Therefore, this study was aimed at determining and analyzing the internal and external environment of Djuanda Forest Park as well as formulating the marketing strategies to increase the number of visitors. This study first set the internal and external factors and formulated the SWOT Matrix. The analysis results based on the internal-external analysis suggested that the strategic position of the forest park lies in cell V (five) by which the applied strategies are to hold and maintain through the market penetration and product development. The SWOT analysis generates several strategies that can be grouped into market penetration and product development